Age-Related Changes in Cognition, Plasma Levels of Brain-Derived Neurotrophic Factors and Selected Indices of Inflammation in Adults at Different Decades of Life (Nigerian Journal of Physiological Sciences, 2024)
Ageing is associated with neurological disorders that are characterized by cognitive impairment. Reports have shown that brain-derived neurotrophic factor (BDNF) is involved in neurogenesis and neuroplasticity. Similarly, chronic inflammation-associated with ageing plays important roles in immunosenescence. However, there is the dearth of information on age-related changes in BDNF level and inflammation. This study was thus, designed to determine cognition, plasma levels of BDNF and selected indices of inflammation in adults at different decades of life. Eighty-eight adults sub-divided into 4 groups; Group I (30 – 39 years), Group II (40 – 49 years), Group III (50 – 59 years) and Group IV (≥60 years) were enrolled into this cross-sectional study. Cognitive function was assessed using the Mini-mental state examination (MMSE). Plasma levels of BDNF and nitric oxide (NO) were determined using ELISA and spectrophotometry. White blood cell count and differentials were done using standard methods and neutrophil-lymphocyte ratio (NLR) was calculated appropriately. There was significant progressive reduction in cognitive score and plasma levels of BDNF as decades of life increase. The neurocognitive scores were significantly higher in Group I, Group II, and Group III compared with Group IV. Similarly, the median plasma level of BDNF was significantly higher in Group I compared with Groups III and IV. Also, the mean mixed count was significantly higher in Group IV compared with Group I while the mean plasma level of NO was significantly higher in Groups II and III compared with Group I. Regression analysis showed that age negatively related with cognition (R2 = 0.522, p = 0.000) and BDNF level (R2 = 0.095, p = 0.003). Furthermore, BDNF had significant positive correlation with the neurocognitive score in Group I. There is progressive reduction in plasma BDNF level and cognitive score with increasing decades of life. This may indicate that plasma BDNF level could predict susceptibility to neurocognitive dysfunction as ageing progresses.